Dynamics of Social Change in Sundane Society: Between Tradition and Modernity in Cireundeu Traditional Village, Cimahi - Ortho Wiria Razak; Encup Supriatna (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study aims to analyze the dynamics of social change within the Cireundeu Traditional Village community in Cimahi, a Sundanese community that maintains tradition amidst modernity. This village is known for its cassava-based food security system (rasi) and Sundanese Wiwitan traditional values, which are still practiced in social life. The research used a qualitative approach with a descriptive case study design through non-participatory field observation, visual documentation, and literature review. The results show that modernization in the form of urbanization, digital technology, and cultural tourism activities does not erase tradition but rather encourages a process of selective adaptation and value negotiation. Core traditions such as rasi consumption and ritual practices are maintained, while non-essential aspects are adapted to contemporary needs. These findings indicate that social change in the Cireundeu Traditional Village is non-linear and represents a form of localized modernity, where cultural identity is reproduced through contextual adaptation mechanisms